WASTE PROBLEM, SECOND LIFE OF WA DEVELOPMENT OF AGRICULTURE ROLE OF MARKETING - Болтаева, Шахноз (Центр Научных Публикаций (buxdu.uz), 2024)
The article contains analyzes of various statistics of waste in Uzbekistan, as well as research on waste recycling and waste reduction in the last 4 years (2019, 2020, 2021, 2022). It also talks about the experience of the leading countries in waste recycling. This article also includes innovations in the field of reproduction.